Kawin Paksa Perspektif Sosiologis dan Psikologis - Ahmad Munir (Justicia Islamica, 2008)
This study aims to analyze the practice of forced marriage from sociological and psychological perspectives, as well as its impact on individuals and society. Using qualitative methods and a literature review approach as well as supporting empirical data, this study examines the socio-cultural factors that perpetuate forced marriage, such as the pressure of tradition, patriarchy, and community norms. Psychologically, this study reveals the negative impact of forced marriage on the mental health of victims, such as trauma, depression, and a decline in quality of life. The results of the study show that forced marriage not only violates the individual's right to freedom of choice of partner, but also causes long-term damage to the social and emotional development of the victim. This study emphasizes the importance of a multidisciplinary approach in dealing with the issue of forced marriage, as well as the need for stronger education, regulation, and legal protection.